Prospective evaluation of screening infertile women using clomiphene citrate challenge test in tertiary care centre of Chengalpattu, Tamil Nadu - Raj, Aneesha; Santhanalakshmi, C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The clomiphene citrate challenge test is a sensitive tool for predicting the ovarian reserve and fertility. Thus, we studied the ovarian reserve in infertile patients using the clomiphene citrate challenge test to analyse the outcomes of the study (pregnancy). Methods: This study included 30 patients with OPD from the Department of Obstetrics and Gynecology at Karpaga Vinayaga Medical College. The study used an Esaote ultrasound machine (Model MyLabSix) as the primary instrument. Infertile women were screened using the Clomiphene Citrate Challenge Test. Results: In 30 patients undergoing a prospective evaluation using the clomiphene citrate challenge test, the mean age was 31.27±2.38 years, with a BMI of 23.89±3.11. The average duration of infertility was 6.30±2.15 years. Primary infertility was observed in 90.0% (27/30) of participants, while 13.3% (4/30) had secondary infertility. Menstrual irregularities included regular cycles (43.3%), irregular cycles (46.7%), heavy bleeding (10.0%), and dysmenorrhea (3.3%). Urine pregnancy test results indicated 60.0% negative and 40.0% positive outcomes. Hormonal assessments showed similar cycle day 3 estradiol levels (p = 0.578), cycle day 3 FSH levels (p = 0.236), cycle day 10 FSH levels (p = 0.933), and antral follicle counts (p = 0.99) between primary and secondary infertility groups. Additionally, there was no significant difference in the distribution of infertility types by UPT result (p = 0.661). Conclusions: The findings of this study highlight the significance of assessing the ovarian reserve as a crucial factor in predicting pregnancy outcomes. Understanding the ovarian reserve aids clinicians in tailoring personalised treatment strategies for infertility management.